Land development as a potential factor of vulnerability. Challenges in Greece’s spatial planning system - Triantis, Loukas (Technical Annals, 2025)
This paper focuses on the concept of vulnerability and explores its entanglements with spatial planning and land development. On the one hand, it traces how vulnerability has been introduced into the legislative framework of climate policies and spatial planning in Greece over the last decade. On the other hand, the paper highlights aspects of vulnerability inextricably entwined with processes of land development in Greece, path dependencies, and contemporary transformations. This dual exploration aims to argue that to address vulnerability in space, merely responding to emergencies and disasters is not enough. Instead, vulnerability should be understood in the context of much more complex, enduring factors that are intertwined with modes and processes of land development. Also, in accordance to innovative international experiences, tackling vulnerability can be a creative field for formulating innovative spatial policies.